```Question 336336

{{{sqrt(4*11*x^4*y^3)}}} Factor {{{44}}} into {{{4*11}}}

{{{sqrt(4*11*x^2*x^2*y^3)}}} Factor {{{x^4}}} into {{{x^2*x^2}}}

{{{sqrt(4*11*x^2*x^2*y^2*y)}}} Factor {{{y^3}}} into {{{y^2*y}}}

{{{sqrt(4)*sqrt(11)*sqrt(x^2)*sqrt(x^2)*sqrt(y^2)*sqrt(y)}}} Break up the square root using the identity {{{sqrt(A*B)=sqrt(A)*sqrt(B)}}}.

{{{2*sqrt(11)*sqrt(x^2)*sqrt(x^2)*sqrt(y^2)*sqrt(y)}}} Take the square root of {{{4}}} to get {{{2}}}.

{{{2*sqrt(11)*x*x*sqrt(y^2)*sqrt(y)}}} Take the square root of {{{x^2}}} to get {{{x}}}.

{{{2*sqrt(11)*x*x*y*sqrt(y)}}} Take the square root of {{{y^2}}} to get {{{y}}}.

{{{2x^2y*sqrt(11y)}}} Rearrange and multiply the terms.

==================================================

So {{{sqrt(44*x^4*y^3)}}} simplifies to {{{2x^2y*sqrt(11y)}}}

In other words, {{{sqrt(44*x^4*y^3)=2x^2y*sqrt(11y)}}} where every variable is non-negative.

If you need more help, email me at <a href="mailto:jim_thompson5910@hotmail.com?Subject=I%20Need%20Algebra%20Help">jim_thompson5910@hotmail.com</a>

Also, feel free to check out my <a href="http://www.freewebs.com/jimthompson5910/home.html">website</a>.

Jim```